Pelatihan keterampilan pencegahan perilaku penyalahgunaan narkoba bagi siswa SD dan SMP di Yogyakarta - Yayi Suryo Prabandari (Berita Kedokteran Masyarakat (BKM), 2005)
Background and Objective: This study was aimed at assessing the effectiveness of a prevention skills training of drugs abuse to deter the initiation of using drugs among elementary and junior high school students in Yogyakarta. The prevention skills training were carried out among students and their parents. Method: An experimental study using pre test-post test control group design was used to assess the effectiveness of prevention skills training of drug abuse. Participants of this study were 242 grade 5 Primary School students and grade 2 Junior High School students, as well as their parents. Knowledge about the harm of drug, attitude toward drug use and intention of using drug were measured by questionnaire. Data were analysed by independent and paired t-tests. Results: There were differences of knowledge about the harm of drug, attitude toward drug use and intention for using drug between experimental and control group in the post test among elementary school students. However, the difference of attitude toward drug use and intention for using drug were not found between experimental and control group among junior high school students. Within the paired West, the result indicated that there were differences of knowledge of the harm of drug between pre test and post test among elementary and junior high school. Moreover, there was a difference of attitude toward using drug between pre test and post test among elementary school students, while the difference was not found among junior high school students. The intention for not using drug was not significantly different between pre test and post test among two groups (elementary and junior high school students). Conclusion: An intervention could not be expected because the implementation of prevention skills training of drugs abuse could not be carried out as it was planned. The main obstacle was because each school has their own relatively tied academic schedule. It might be better if the prevention skills training of drugs abuse were included in the school curriculum. Keywords: prevention skills training, drugs abuse